Characterization of Defects in Curved Composite Structures Using Active Infrared Thermography. (2016) - Pastuszak, Przemysław Daniel
Abstract: The paper presents thermographic studies of curved composite panels (GFRP) with subsurface defects. Two types of defects are analysed: 1) artificial, created by inserting Teflon stripe between individual layers of a laminate during manufacturing stage and 2) real, caused by static loading tests. The phenomena observed during the experiments can be successfully simulated by means of the FEM which considerably expands capabilities of standard AIRT. ANSYS package was used to simulate transient heat transfer in 3D model with embedded various defects. Results confirmed the validity of the FE model in comparison to conducted experiments. Analysis of temperature distribution on investigated surfaces provides the opportunity to determine the geometry of subsurface defects.